Recreational microplastics as emerging pollutants: effects of crumb rubber leachate across ecosystems - Sharon T. Pochron; Xiayan Ye; Amith S. Maroli; Arjun K. Venkatesan; Samy Sasoun; Thomas J. Gaylor; Mary Girgis; Morgan A. Jacobellis; Alec Miranda; Johanna A. Mitra; Grace Van Gelder; Samantha H. Byrne; et al. (Chemosphere, 2026)

A Numerical Study of Eastern Oyster (Crassostrea virginica) Larval Growth and Dispersal in Barataria Estuary, Louisiana, USA - Zhengchen Zang; Z. George Xue; Shaye E. Sable; Megan K. La Peyre; Kenneth A. Rose; Timothy A. Stephens; Brady Carter; David C. Lindquist; Yanda Ou; Ziyan Lei (Estuaries and Coasts, 2026)

Anatomy of Eurotamandua joresi (Mammalia) from Grube Messel, Germany, based on computed tomography, and implications for its relationships. Part I: Background and forelimb - Kenneth D. Rose; Renate Rabenstein; Jörg Habersetzer; Timothy J. Gaudin (Palaeobiodiversity and Palaeoenvironments, 2026)
Micro-computed tomography of the unique skeleton of Eurotamandua joresi Storch, 1981 (middle Eocene, Grube Messel)—initially described as the oldest myrmecophagid and the only known Old World xenarthran—reveals details of its skeletal anatomy that were previously obscured, enabling close comparative study for the first time. In this report we focus on the forelimb. The segmentation of scapula, humerus, radius, ulna, carpals, metacarpals and phalanges reveals exceptional specializations for scratch digging. These include numerous features that are strikingly similar to those of palaeanodonts, and to a lesser degree manids, but which contrast sharply with those of the xenarthrans Tamandua and Dasypus . Other features once thought to ally Eurotamandua with xenarthrans, such as a secondary scapular spine, absence of teeth, and a tubular snout, are not restricted to Xenarthra. The new forelimb characters are here incorporated into a phylogenetic analysis that includes xenarthrans, pholidotans, and palaeanodonts. This new analysis provides compelling evidence that Eurotamandua is related to Palaeanodonta (Laurasiatheria: Pholidotamorpha) rather than to Xenarthra, thus separating it from xenarthrans at the superordinal level. Consequently, there is no evidence that Xenarthra ever reached the Old World.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Experimental determination of equilibrium sulfur isotope fractionation factors in the gas-silicate melt-sulfide liquid system - Shashank Prabha-Mohan; Kenneth T. Koga; Diego F. Narváez; Estelle F. Rose-Koga; Jabrane Labidi (Geochimica et Cosmochimica Acta, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

Deeper, faster, stronger? Extreme magma ascent rates and explosive eruption metrics at Stromboli volcano (Italy) - Guillaume Georgeais; Yves Moussallam; Estelle F. Rose-Koga; Kenneth T. Koga; Lucia Gurioli; Andrew Harris; Nicole Métrich; Antonella Bertagnini; Maximilien Verdier-Paoletti; Marco Pistolesi (Bulletin of Volcanology, 2025)

Evaluation of Fusarium ear rot and fumonisins in twenty Zambian maize genotypes - Doreen Malekano Chomba; Patrick Chiza Chikoti; Paul Walubita Kachapulula; Kenneth Kajarayekha M'siska; Altus Viljoen; Lindy Joy Rose (Crop Protection, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Benthic foraminiferal Mg/Ca response across the Aptian-Albian Boundary Interval at DSDP Site 511 (Falkland Plateau) - Barbara Balestra; Brian Huber; Jonathan Chen; Gabriela A. Farfan; Kenneth G. MacLeod; Timothy Rose; Adina Paytan; Timothy Gooding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Volatiles in olivine-hosted melt inclusions from a rejuvenated Oʻahu tephra: Degree of melting controls the primary melt CO2 content—And extent of H2O degassing—Of OIB - Olivia E. Anderson; Matthew G. Jackson; James Dottin; Sunna Harðardóttir; Kenneth T. Koga; Gareth Seward; John Cottle; Estelle F. Rose-Koga; Natália Gauer-Pasqualon (Chemical Geology, 2025)

Leveraging Maker Learning in STEM to Promote Children’s Interest in Cancer Research: A Pilot Program - Kenneth P. Tercyak; Mary Rose Yockel; Jacqueline Eyl; Chiranjeev Dash; Dorothy Jones-Davis; Marcelo M. Sleiman; Liza Manfred; Dia Stone; Karen Howenstein; Denise Flessate Harley; Mingqian Liu; Catherine J. Scharon; et al. (Journal of Cancer Education, 2024)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Ecological Interactions Between Non-Native American Shad and Pacific Salmon: The Columbia River Case Study - Thomas P. Quinn; John Epifanio; Peter B. Moyle; Stan Gregory; Daniel J. Hasselman; Erik Merrill; Kenneth Rose; Thomas F. Turner; Thomas C. Wainwright (Reviews in Fisheries Science & Aquaculture, 2024)

ATSEA: A Regional Collaboration to Address Transboundary Threats to Ecosystems for Human Well-Being in the Arafura and Timor Seas - Handoko Adi Susanto; Casandra Tania; Cristine Ingrid Narcise; Kathrine Rose Aguiling; Deti Triani; Dwi Ariyoga Gautama; Kenneth Yhuanje; Expedito Maria Belo (Coastal Management, 2024)

Extensive H2O degassing in deeply erupted submarine glasses inferred from Samoan melt inclusions: The EM2 mantle source is damp, not dry - Olivia E. Anderson; Matthew G. Jackson; Ayla S. Pamukçu; Estelle F. Rose-Koga; Véronique Le Roux; Frieder Klein; Kenneth T. Koga; Glenn A. Gaetani; Allison A. Price (Chemical Geology, 2024)

The breeding ecology of the Agulhas Long-billed Lark: an endemic bird dependent on the remnant Renosterveld of the Western Cape Province, South Africa - Sanjo Rose; Robert Leslie Thomson; Alan Tristam Kenneth Lee; Peter Geoffrey Ryan (Journal of Ornithology, 2024)
The Agulhas Long-billed Lark Certhilauda brevirostris is restricted to the Agulhas Plain, South Africa, a region extensively transformed for crop production and sheep grazing. We present data on nest and egg characteristics, clutch and brood size, parental care and breeding success previously undescribed for this species. During field surveys in 2020 and 2021, 29 nests were located. Of these, 16 were monitored by camera traps. Laying started in late winter (July) and continued until early summer (late November). Most nests (66%) were in Renosterveld, a unique vegetation component of the Fynbos Biome, with the remainder in human-modified landscapes. Female larks were responsible for nest construction and incubation. Both sexes provisioned nestlings, with provisioning rate related to nestling age and time of day but not brood size. Breeding success was low, with only 14% of nests fledging any young. Only one repeat nesting attempt following a predation event was observed, but the attempt was abandoned. Nest predation was the main cause of nest failure, with eight species of nest predators identified. An apparent preference for nesting in Renosterveld highlights the need for protection of this endangered habitat type. As a ground-nesting species in an agriculturally transformed landscape, this lark faces numerous threats associated with habitat loss, altered predation pressure, exposure to pesticides and disturbance at nest sites.

An empirical relation between velocity, mass discharge rate and vent area for normal through paroxysmal eruptions at Stromboli - Guillaume Georgeais; Andrew J. L. Harris; Yves Moussallam; Kenneth T. Koga; Estelle F. Rose-Koga (Bulletin of Volcanology, 2024)

Management strategy of the naked carp (Gymnocypris przewalskii) in the Qinghai lake using matrix population modeling - Chubin Weng; Mengzhen Xu; Fakai Lei; Kenneth A. Rose (Journal of Environmental Management, 2023)

Searching for Oxygen: Dynamic Movement Responses of Juvenile Spot (Leiostomus xanthurus) in an Intermittently Hypoxic Estuary - J. Kevin Craig; Klaus B. Huebert; Kenneth A. Rose; James A. Rice; Damian C. Brady (Estuaries and Coasts, 2023)

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

Correction to: Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)

Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)
Partial body cryotherapy (PBC) is proposed to alleviate symptoms of exercise-induced muscle damage (EIMD) by reducing associated inflammation. No studies have assessed acute PBC exposure on peripheral blood mononuclear cell mobilisation or compared these with cold water immersion (CWI), which may inform how PBC impacts inflammatory processes. This trial examined the impact of a single PBC exposure on circulating peripheral blood mononuclear cells compared to CWI or a control. 26 males were randomised into either PBC (3 min at − 110 to − 140 °C), CWI (3 min at 9 °C), or control (3 min at 24 °C), with blood samples, heart rate, and blood pressure taken before and after exposure. Cytometric analysis determined that CD8 + T-cell populations were significantly elevated after treatments, with PBC increasing CD8 + T cells to a greater degree than either CWI or CON. Natural killer cell counts were also elevated after PBC, with the increase attributed specifically to the CD56 lo CD16 + cytotoxic subset. This provides the first evidence for the effect of PBC exposure on redistribution of immune cells. An increase in circulating leukocyte subsets such as CD8 + T cells and CD56 lo CD16 + natural killer cells suggests that PBC may induce a transient mobilisation of lymphocytes. PBC may thus enable a more efficient trafficking of these cells from the circulation to the site of initial cellular insult from exercise, potentially accelerating the process of cellular recovery. This provides novel evidence on the use of PBC as a recovery treatment and may also have applicability in other clinical settings involving the recovery of damaged skeletal muscle.

Phylogeography and genetic variation in Western Jacob's ladder ( Polemonium occidentale ) provide insights into the origin and conservation of rare species in the Great Lakes region - Jeffrey P. Rose; Kenneth J. Sytsma (Molecular Ecology, 2023)
The perennial herb Western Jacob's Ladder ( Polemonium occidentale , Polemoniaceae) is widespread in the mountains of western North America but reappears as a disjunct in the Great Lakes Region in Minnesota and Wisconsin, USA as the narrow endemic P. occidentale subsp. lacustre . This distribution is shown by a diverse assemblage of angiosperms. It has been hypothesized that these species became isolated just after the Last Glacial Maximum, but this has not been tested. Additionally, the genetic diversity and population connectivity of the endemic Great Lakes flora has been understudied, with important conservation implications. Using genotyping‐by‐sequencing, we examined the relationship of P. occidentale subsp. lacustre to its closest relatives, relationships among all known populations, and genetic diversity within these populations. Polemonium occidentale subsp. lacustre represents an isolated, unique lineage that diverged from its closest relatives 1.3 Ma and arrived in the Great Lakes Region by at least 38 ka. Nearly all extant populations diverged prior to the Last Glacial Maximum, are genetically distinct, and show little within‐population genetic diversity. Clonality may mitigate reduction in diversity due to drift. Mixed population signal between Wisconsin and some Minnesota populations may be due to gene flow during the Late Pleistocene. While populations of P. occidentale subsp. lacustre may be relictual from a now extinct western relative, it is best treated as a distinct species. Conservation efforts should focus more on ensuring that current populations remain rather than maintaining large populations sizes across a few populations. However, encouraging habitat heterogeneity may accomplish both simultaneously.

The role of inner nuclear membrane proteins in tumourigenesis and as potential targets for cancer therapy - Maddison Rose; Joshua T. Burgess; Kenneth O’Byrne; Derek J. Richard; Emma Bolderson (Cancer and Metastasis Reviews, 2022)
Despite significant advances in our understanding of tumourigenesis and cancer therapeutics, cancer continues to account for 30% of worldwide deaths. Therefore, there remains an unmet need for the development of cancer therapies to improve patient quality of life and survival outcomes. The inner nuclear membrane has an essential role in cell division, cell signalling, transcription, cell cycle progression, chromosome tethering, cell migration and mitosis. Furthermore, expression of several inner nuclear membrane proteins has been shown to be frequently altered in tumour cells, resulting in the dysregulation of cellular pathways to promote tumourigenesis. However, to date, minimal research has been conducted to investigate how targeting these dysregulated and variably expressed proteins may provide a novel avenue for cancer therapies. In this review, we present an overview of the involvement of the inner nuclear membrane proteins within the hallmarks of cancer and how they may be exploited as potent anti-cancer therapeutics.

Editorial: Habitat and distribution models of marine and estuarine species: Advances for a sustainable future - Mary C. Fabrizio; Mark J. Henderson; Kenneth Rose; Pierre Petitgas (Frontiers in Marine Science, 2022)

Transport Processes in the Gulf of Mexico Along the River-Estuary-Shelf-Ocean Continuum: a Review of Research from the Gulf of Mexico Research Initiative - Dubravko Justić; Villy Kourafalou; Giulio Mariotti; Songjie He; Robert Weisberg; Yannis Androulidakis; Christopher Barker; Annalisa Bracco; Brian Dzwonkowski; Chuanmin Hu; Haosheng Huang; Gregg Jacobs; et al. (Estuaries and Coasts, 2022)
Estuarine and coastal geomorphology, biogeochemistry, water quality, and coastal food webs in river-dominated shelves of the Gulf of Mexico (GoM) are modulated by transport processes associated with river inputs, winds, waves, tides, and deep-ocean/continental shelf interactions. For instance, transport processes control the fate of river-borne sediments, which in turn affect coastal land loss. Similarly, transport of freshwater, nutrients, and carbon control the dynamics of eutrophication, hypoxia, harmful algal blooms, and coastal acidification. Further, freshwater inflow transports pesticides, herbicides, heavy metals, and oil into receiving estuaries and coastal systems. Lastly, transport processes along the continuum from the rivers and estuaries to coastal and shelf areas and adjacent open ocean (abbreviated herein as “river-estuary-shelf-ocean”) regulate the movements of organisms, including the spatial distributions of individuals and the exchange of genetic information between distinct subpopulations. The Gulf of Mexico Research Initiative (GoMRI) provided unprecedented opportunities to study transport processes along the river-estuary-shelf-ocean continuum in the GoM. The understanding of transport at multiple spatial and temporal scales in this topographically and dynamically complex marginal sea was improved, allowing for more accurate forecasting of the fate of oil and other constituents. For this review, we focus on five specific transport themes: (i) wetland, estuary, and shelf exchanges; (ii) river-estuary coupling; (iii) nearshore and inlet processes; (iv) open ocean transport processes; and (v) river-induced fronts and cross-basin transport. We then discuss the relevancy of GoMRI findings on the transport processes for ecological connectivity and oil transport and fate. We also examine the implications of new findings for informing the response to future oil spills, and the management of coastal resources and ecosystems. Lastly, we summarize the research gaps identified in the many studies and offer recommendations for continuing the momentum of the research provided by the GoMRI effort. A number of uncertainties were identified that occurred in multiple settings. These include the quantification of sediment, carbon, dissolved gasses and nutrient fluxes during storms, consistent specification of the various external forcings used in analyses, methods for smooth integration of multiscale advection mechanisms across different flow regimes, dynamic coupling of the atmosphere with sub-mesoscale and mesoscale phenomena, and methods for simulating finer-scale dynamics over long time periods. Addressing these uncertainties would allow the scientific community to be better prepared to predict the fate of hydrocarbons and their impacts to the coastal ocean, rivers, and marshes in the event of another spill in the GoM.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Editorial: Ecological Applications of Earth System Models and Regional Climate Models - Rebecca G. Asch; Johnna M. Holding; Darren J. Pilcher; Sara Rivero-Calle; Kenneth A. Rose (Frontiers in Marine Science, 2021)

Projected Shifts in 21st Century Sardine Distribution and Catch in the California Current - Jerome Fiechter; Mercedes Pozo Buil; Michael G. Jacox; Michael A. Alexander; Kenneth A. Rose (Frontiers in Marine Science, 2021)
Predicting changes in the abundance and distribution of small pelagic fish species in response to anthropogenic climate forcing is of paramount importance due to the ecological and socioeconomic importance of these species, especially in eastern boundary current upwelling regions. Coastal upwelling systems are notorious for the wide range of spatial (from local to basin) and temporal (from days to decades) scales influencing their physical and biogeochemical environments and, thus, forage fish habitat. Bridging those scales can be achieved by using high-resolution regional models that integrate global climate forcing downscaled from coarser resolution earth system models. Here, “end-to-end” projections for 21st century sardine population dynamics and catch in the California Current system (CCS) are generated by coupling three dynamically downscaled earth system model solutions to an individual-based fish model and an agent-based fishing fleet model. Simulated sardine population biomass during 2000–2100 exhibits primarily low-frequency (decadal) variability, and a progressive poleward shift driven by thermal habitat preference. The magnitude of poleward displacement varies noticeably under lower and higher warming conditions (500 and 800 km, respectively). Following the redistribution of the sardine population, catch is projected to increase by 50–70% in the northern CCS and decrease by 30–70% in the southern and central CCS. However, the late-century increase in sardine abundance (and hence, catch) in the northern CCS exhibits a large ensemble spread and is not statistically identical across the three downscaled projections. Overall, the results illustrate the benefit of using dynamical downscaling from multiple earth system models as input to high-resolution regional end-to-end (“physics to fish”) models for projecting population responses of higher trophic organisms to global climate change.

Locomotor Behavior and Body Mass of Paramys delicatus (Ischyromyidae, Rodentia) and Commentary on Other Early North American Paramyines - Kristen A. Prufrock; Christopher B. Ruff; Kenneth D. Rose (Journal of Mammalian Evolution, 2021)

How to turn off a lava lake? A petrological investigation of the 2018 intra-caldera and submarine eruptions of Ambrym volcano - Yves Moussallam; Etienne Médard; Guillaume Georgeais; Estelle F. Rose-Koga; Kenneth T. Koga; Bernard Pelletier; Philipson Bani; Tara L. Shreve; Raphael Grandin; Marie Boichu; Dan Tari; Nial Peters (Bulletin of Volcanology, 2021)

Toward a better understanding of fish‐based contribution to ocean carbon flux - Grace K. Saba; Adrian B. Burd; John P. Dunne; Santiago Hernández‐León; Angela H. Martin; Kenneth A. Rose; Joseph Salisbury; Deborah K. Steinberg; Clive N. Trueman; Rod W. Wilson; Stephanie E. Wilson (Limnology and Oceanography, 2021)
Fishes are the dominant vertebrates in the ocean, yet we know little of their contribution to carbon export flux at regional to global scales. We synthesize the existing information on fish‐based carbon flux in coastal and pelagic waters, identify gaps and challenges in measuring this flux and approaches to address them, and recommend research priorities. Based on our synthesis of passive (fecal pellet sinking) and active (migratory) flux of fishes, we estimated that fishes contribute an average (± standard deviation) of about 16.1% (± 13%) to total carbon flux out of the euphotic zone. Using the mean value of model‐generated global carbon flux estimates, this equates to an annual flux of 1.5 ± 1.2 Pg C yr −1 . High variability in estimations of the fish‐based contribution to total carbon flux among previous field studies and reported here highlight significant methodological variations and observational gaps in our present knowledge. Community‐adopted methodological standards, improved and more frequent measurements of biomass and passive and active fluxes of fishes, and stronger linkages between observations and models will decrease uncertainty, increase our confidence in the estimation of fish‐based carbon flux, and enable identification of controlling factors to account for spatial and temporal variability. Better constraints on this key component of the biological pump will provide a baseline for understanding how ongoing climate change and harvest will affect the role fishes play in carbon flux.

Dynamics of anchovy and sardine populations in the Canary Current off NW Africa: Responses to environmental and climate forcing in a climate‐to‐fish ecosystem model - José C. Sánchez‐Garrido; Jerome Fiechter; Kenneth A. Rose; Francisco E. Werner; Enrique N. Curchitser (Fisheries Oceanography, 2021)
A 50‐year‐long (1958–2008) historical simulation of a climate‐to‐fish ecosystem model for anchovy ( Eugralis encrasicolus ) and sardine ( Sardina pilchardus ) populations in the upwelling ecosystem off NW Africa is revisited and analyzed. Anchovy and sardine annual adult abundances were correlated at interannual and decadal time scales in the historical run. A three‐step analysis method applied unraveled the environmental and life stage‐specific drivers underlying the bottom‐up mechanisms responsible for the simulated variability in anchovy and sardine populations. Changes in anchovy adult abundance were primarily controlled by larval survival, prey availability, and local upwelling strength, whereas sardine adult abundance was controlled by age‐1 growth affecting age‐2 fecundity and egg production via prey availability. Despite different diet preferences, the common sensitivity of anchovy and sardine to prey availability had a synchronizing effect on the two populations, with both anchovy and sardine doing better during years of higher plankton biomass and colder ocean temperatures. Analysis of potential links with modes of climate variability showed that anchovy dynamics were more tightly connected to the AMO while sardine dynamics were correlated to the NAO. This difference stemmed from the vulnerability of the anchovy population to enhanced coastal upwelling causing increased larval drift mortality. Finally, based on an earlier, similar modeling study for the Californian anchovy and Pacific sardine, we argue that the relatively warmer habitat off NW Africa compared to the coastal region off central California is a key feature explaining synchronous populations in the Canary Current versus out‐of‐phase anchovy and sardine cycles in the California Current.

Using Multiple Ecological Models to Inform Environmental Decision-Making - Kristy A. Lewis; Kenneth A. Rose; Kim de Mutsert; Shaye Sable; Cameron Ainsworth; Damian C. Brady; Howard Townsend (Frontiers in Marine Science, 2021)
Coastal ecosystems are experiencing degradation from compound impacts of climate change and multiple anthropogenic disturbances. These pressures often act synergistically and complicate designing effective conservation measures; consequently, large-scale coastal restoration actions become a wicked problem. The purpose of this study was to use two different food web models in a coordinated manner to inform resource managers in their assessment of the ecological effects of a large-scale marsh restoration project. A team was formed that included the model developers and outside scientists, who were asked to use available model results of the calibrated simulations of an Ecopath with Ecosim (EwE) model and a Comprehensive Aquatic Systems Model (CASM), both designed to describe the structure and energetics of the Barataria Bay, Louisiana, United States food web. Both models offer somewhat different depictions of the predator-prey and competitive interactions of species within the food web, and how environmental conditions affect the species biomass pools and energetics. Collectively, the team evaluated the strengths of each model and derived a common set of indicator variables from model outputs that provided information on the structure and energy flow of the simulated food web. Considering the different modeling structures and calibration approaches, indicators were interpreted within and between models. Use of both models enabled a robust determination that: (1) Detritus plays a vital role in the energetics of the system; (2) The food web responds to spring high flow seasons by increasing productivity through specific, dominant pathways; (3) The trophic pyramid is truncated; (4) Compared to other estuaries, this system has redundant pathways for energy transfer. These findings indicate that the food web appears to be resilient to disturbance because of a detritus energy reserve, most consumer biomass consists of low trophic level, high turnover species, and redundant energy pathways exist. This information provides context to decision-makers for assessing possible basin-scale impacts on fish and shellfish resources of a proposed large-scale restoration project. The use of multiple models in a coordinated but not overly constrained way, as demonstrated here, provides a significant step toward co-production of knowledge for use in resource management decisions.

Persistent gas emission originating from a deep basaltic magma reservoir of an active volcano: the case of Aso volcano, Japan - Masataka Kawaguchi; Toshiaki Hasenaka; Kenneth T. Koga; Estelle F. Rose-Koga; Atsushi Yasuda; Natsumi Hokanishi; Yasushi Mori; Kenji Shimizu; Takayuki Ushikubo (Contributions to Mineralogy and Petrology, 2021)

Potential establishment and ecological effects of bighead and silver carp in a productive embayment of the Laurentian Great Lakes - Lori N. Ivan; Doran M. Mason; Hongyan Zhang; Edward S. Rutherford; Tim Hunter; Shaye Sable; Aaron T. Adamack; Kenneth Rose (Biological Invasions, 2020)
Bighead carp H . nobilis and silver carp Hypothalmichthys molitrix (collectively bigheaded carps, BHC) are invasive planktivorous fishes that threaten to enter the Laurentian Great Lakes and disrupt food webs. To assess the likelihood of BHC establishment and their likely effects on the food web of Saginaw Bay, Lake Huron, we developed a multi-species individual-based bioenergetics model that tracks individual bighead and silver carp, four key fish species, and seven prey biomass groups over 50 years. The model tracks the daily consumption, mortality and growth of all individuals and the biomass dynamics of interacting prey pools. We ran simulation scenarios to determine the likelihood of BHC establishment under initial introductions from 5 to 1 million yearling and older individuals, and assuming variable age-0 carp survival rates (high, intermediate, and low). We bounded the survival of age-0 BHC as recruitment continues to be one of the biggest unknowns. We also simulated the potential effects of an established population of 1 million bighead carp or silver carp assuming variation in age-0 survival. Results indicated that as few as 10 BHC could establish a population assuming high or intermediate age-0 survival, but at least 100,000 individuals were needed to establish a population assuming low age-0 survival. BHC had negative effects on plankton and planktivorous fish biomass, which increased with BHC density. However, piscivorous walleye Sander vitreus appeared to benefit from BHC establishment. The potential for BHC to establish and affect ecologically and economically important fish species in Saginaw Bay is a cause for concern.

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Fast ascent rate during the 2017–2018 Plinian eruption of Ambae (Aoba) volcano: a petrological investigation - Yves Moussallam; Estelle F. Rose-Koga; Kenneth T. Koga; Etienne Médard; Philipson Bani; Jean-Luc Devidal; Dan Tari (Contributions to Mineralogy and Petrology, 2019)

Modeling Fish Movement in 3-D in the Gulf of Mexico Hypoxic Zone - Elizabeth LaBone; Dubravko Justic; Kenneth Rose; Lixia Wang; Haosheng Huang (Estuaries and Coasts, 2019)

Modeling Quantitative Value of Habitats for Marine and Estuarine Populations - Romuald N. Lipcius; David B. Eggleston; F. Joel Fodrie; Jaap van der Meer; Kenneth A. Rose; Rita P. Vasconcelos; Karen E. van de Wolfshaar (Frontiers in Marine Science, 2019)

Mastication and enamel microstructure in Cambaytherium, a perissodactyl-like ungulate from the early Eocene of India - Wighart von Koenigswald; Kenneth D. Rose; Luke T. Holbrook; Kishor Kumar; Rajendra S. Rana; Thierry Smith (PalZ, 2018)

Climate variability and sardine recruitment in the California Current: A mechanistic analysis of an ecosystem model - Dimitrios V. Politikos; Enrique N. Curchitser; Kenneth A. Rose; David M. Checkley; Jerome Fiechter (Fisheries Oceanography, 2018)
Recruitment varies substantially in small pelagic fish populations. Understanding of the mechanisms linking environment to recruitment is essential for the effective management of fisheries resources. In this study, we used a fully coupled end‐to‐end ecosystem model to study the effect of climate variability on sardine recruitment in the California Current System during 1965–2006. Ocean variability was represented by ROMS hydrodynamic and NEMURO biogeochemical models, and sardine population dynamics was simulated through a full life cycle individual‐based model. Model analysis was designed to elucidate how changes in abiotic and biotic conditions may impact the spawning habitats, early life stage survival, and ultimately recruitment of sardine. Our findings revealed the importance of spatial processes to shape early life stages dynamics. Shifts in spawning habitats were dictated by the spatial variations in temperature and the behavioral movement of adults. Additionally, the spatial match of eggs with warmer temperatures and larvae with their prey influenced their survival. The northward shifts in spawning locations and the accomplishment of good recruitment in warmer years agreed with existing knowledge. Egg production and survival during egg and yolk‐sac larval stages were key factors to drive the long‐term variations in recruitment. Finally, our analysis provided a quantitative assessment of climate impact on year‐to‐year variation in sardine recruitment by integrating multiple hypotheses.

Constraining magma sources using primitive olivine-hosted melt inclusions from Puñalica and Sangay volcanoes (Ecuador) - Diego F. Narvaez; Estelle F. Rose-Koga; Pablo Samaniego; Kenneth T. Koga; Silvana Hidalgo (Contributions to Mineralogy and Petrology, 2018)

Applying spatiotemporal models to monitoring data to quantify fish population responses to the Deepwater Horizon oil spill in the Gulf of Mexico - Eric J. Ward; Kiva L. Oken; Kenneth A. Rose; Shaye Sable; Katherine Watkins; Elizabeth E. Holmes; Mark D. Scheuerell (Environmental Monitoring and Assessment, 2018)

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 2—Realistic Hypoxia and Eutrophication - Kenneth A. Rose; Sean Creekmore; Dubravko Justić; Peter Thomas; J. Kevin Craig; Rachael Miller Neilan; Lixia Wang; Md Saydur Rahman; David Kidwell (Estuaries and Coasts, 2018)

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 1—Model Description and Idealized Hypoxia - Kenneth A. Rose; Sean Creekmore; Peter Thomas; J. Kevin Craig; Md Saydur Rahman; Rachael Miller Neilan (Estuaries and Coasts, 2018)

Ecosystem modeling in the Gulf of Mexico: current status and future needs to address ecosystem-based fisheries management and restoration activities - Halie O’Farrell; Arnaud Grüss; Skyler R. Sagarese; Elizabeth A. Babcock; Kenneth A. Rose (Reviews in Fish Biology and Fisheries, 2017)

Digital reconstruction of the inner ear of Leptictidium auderiense (Leptictida, Mammalia) and North American leptictids reveals new insight into leptictidan locomotor agility - Irina Ruf; Virginie Volpato; Kenneth D. Rose; Guillaume Billet; Christian de Muizon; Thomas Lehmann (PalZ, 2016)

Ecosystem models for fisheries management: finding the sweet spot - Jeremy S Collie; Louis W Botsford; Alan Hastings; Isaac C Kaplan; John L Largier; Patricia A Livingston; Éva Plagányi; Kenneth A Rose; Brian K Wells; Francisco E Werner (Fish and Fisheries, 2016)
The advent of an ecosystem‐based approach dramatically expanded the scope of fisheries management, creating a critical need for new kinds of data and quantitative approaches that could be integrated into the management system. Ecosystem models are needed to codify the relationships among drivers, pressures and resulting states, and to quantify the trade‐offs between conflicting objectives. Incorporating ecosystem considerations requires moving from the single‐species models used in stock assessments, to more complex models that include species interactions, environmental drivers and human consequences. With this increasing model complexity, model fit can improve, but parameter uncertainty increases. At intermediate levels of complexity, there is a ‘sweet spot’ at which the uncertainty in policy indicators is at a minimum. Finding the sweet spot in models requires compromises: for example, to include additional component species, the models of each species have in some cases been simplified from age‐structured to logistic or bioenergetic models. In this paper, we illuminate the characteristics, capabilities and short‐comings of the various modelling approaches being proposed for ecosystem‐based fisheries management. We identify key ecosystem needs in fisheries management and indicate which types of models can meet these needs. Ecosystem models have been playing strategic roles by providing an ecosystem context for single‐species management decisions. However, conventional stock assessments are being increasingly challenged by changing natural mortality rates and environmentally driven changes in productivity that are observed in many fish stocks. Thus, there is a need for more tactical ecosystem models that can respond dynamically to changing ecological and environmental conditions.

Small-mammal postcrania from the middle Paleocene of Walbeck, Germany - Kenneth D. Rose; Gerhard Storch; Katrin Krohmann (PalZ, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Hydration of mantle olivine under variable water and oxygen fugacity conditions - Glenn A. Gaetani; Julie A. O’Leary; Kenneth T. Koga; Erik H. Hauri; Estelle F. Rose-Koga; Brian D. Monteleone (Contributions to Mineralogy and Petrology, 2014)

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

The importance of Messel for interpreting Eocene Holarctic mammalian faunas - Kenneth D. Rose (Palaeobiodiversity and Palaeoenvironments, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Task-related oxygen uptake and symptoms during activities of daily life in CHF patients and healthy subjects - Martijn A. Spruit; Emiel F. M. Wouters; Rose-Mieke A. Eterman; Kenneth Meijer; Scott S. Wagers; Koen H. P. Stakenborg; Nicole H. M. K. Uszko-Lencer (European Journal of Applied Physiology, 2011)

A review of the NEMURO and NEMURO.FISH models and their application to marine ecosystem investigations - Michio J. Kishi; Shin-ichi Ito; Bernard A. Megrey; Kenneth A. Rose; Francisco E. Werner (Journal of Oceanography, 2011)

Effects of sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor desensitizing agent on alcohol and nicotine self-administration in selectively bred alcohol-preferring (P) rats - Amir H. Rezvani; Susan Slade; Cori Wells; Ann Petro; Lawrence Lumeng; Ting-Kai Li; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Jed E. Rose; Kenneth J. Kellar; et al. (Psychopharmacology, 2010)

Life history correlates and extinction risk of capital-breeding fishes - Henriette I. Jager; Kenneth A. Rose; Anna Vila-Gispert (Hydrobiologia, 2008)

High bat (Chiroptera) diversity in the Early Eocene of India - Thierry Smith; Rajendra S. Rana; Pieter Missiaen; Kenneth D. Rose; Ashok Sahni; Hukam Singh; Lachham Singh (The Science of Nature, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

The Enamel Microstructure of the Early Eocene Pantodont Coryphodonand the Nature of the Zigzag Enamel - Wighart V. Koenigswald; Kenneth D. Rose (Journal of Mammalian Evolution, 2005)

Stock Enhancement and Sea Ranching: Developments, Pitfalls and Opportunities, Second Edition - Kenneth A. Rose (Fish and Fisheries, 2005)

Compensatory density dependence in fish populations: importance, controversy, understanding and prognosis - Kenneth A Rose; James H Cowan; Kirk O Winemiller; Ransom A Myers; Ray Hilborn (Fish and Fisheries, 2001)
Density‐dependent processes such as growth, survival, reproduction and movement are compensatory if their rates change in response to variation in population density (or numbers) such that they result in a slowed population growth rate at high densities and promote a numerical increase of the population at low densities. Compensatory density dependence is important to fisheries management because it operates to offset the losses of individuals. While the concept of compensation is straightforward, it remains one of the most controversial issues in population dynamics. The difficulties arise when going from general concepts to specific populations. Compensation is usually quantified using some combination of spawner–recruit analysis, long‐term field monitoring or manipulative studies, and computer modelling. Problems arise because there are limitations to each of these approaches, and these limitations generally originate from the high uncertainty associated with field measurements. We offer a hierarchical approach to predicting and understanding compensation that ranges from the very general, using basic life‐history theory, to the highly site‐specific, using detailed population models. We analyse a spawner–recruit database to test the predictions about compensation and compensatory reserve that derive from a three‐endpoint life‐history framework designed for fish. We then summarise field examples of density dependence in specific processes. Selected long‐term field monitoring studies, manipulative studies and computer modelling examples are then highlighted that illustrate how density‐dependent processes led to compensatory responses at the population level. Some theoretical and empirical advances that offer hope for progress in the future on the compensation issue are discussed. We advocate an approach to compensation that involves process‐level understanding of the underlying mechanisms, life‐history theory, careful analysis of field data, and matrix and individual‐based modelling. There will always be debate if the quantification of compensation does not include some degree of understanding of the underlying mechanisms.

Eurotamandua and Palaeanodonta: convergent or related? - Kenneth D. Rose (PalZ, 1999)

Simulating smallmouth bass reproductive success in reservoirs - Mark E. Clark; Kenneth A. Rose; James A. Chandler; Tracy J. Richter; Donald J. Orth; Webster Van Winkle (Environmental Biology of Fishes, 1998)